2020
DOI: 10.3390/vaccines8030437
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of Mice with a Novel Trypsin from Trichinella spiralis Elicits the Immune Protection against Larval Challenge

Abstract: Trichinella spiralis is a major foodborne parasite and has a serious threat to meat safety. Development of anti-Trichinella vaccines is prospective to eliminate Trichinella infection in food animal. The aim of this study was to assess the biological properties of a novel T. spiralis trypsin (TsT) and its elicited immune protection against larval challenge. The cDNA sequence of TsT gene was cloned and expressed. Western blotting showed rTsT was identified by infection serum and anti-TsT serum. RT-PCR results re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Ten BALB/c mice were immunized by subcutaneous injection of 20 μg of rTsCatL2 mixed with MONTA-NIDE ™ ISA 61 VG 1:1 (v/v), with one booster immunization three weeks later [43,44]. After another two-week interval, polyclonal antibodies against rTsCatL2 were obtained by collecting blood from mice.…”
Section: Production Of a Mouse Polyclonal Antibodymentioning
confidence: 99%
“…Ten BALB/c mice were immunized by subcutaneous injection of 20 μg of rTsCatL2 mixed with MONTA-NIDE ™ ISA 61 VG 1:1 (v/v), with one booster immunization three weeks later [43,44]. After another two-week interval, polyclonal antibodies against rTsCatL2 were obtained by collecting blood from mice.…”
Section: Production Of a Mouse Polyclonal Antibodymentioning
confidence: 99%
“…Vaccination of mice with rTsASP2 triggered specific humoral and mucosal immune responses, as demonstrated that both specific IgG and sIgA levels were significantly elevated two weeks post vaccination. The IgG1 level was significantly higher than IgG2a, suggested that rTsASP2 emulsified in ISA201 adjuvant elicited a mixed IgG1/ IgG2a antibody response (Yang et al, 2019b;Zhang et al, 2020b). The antibody response was important for the protective immunity, but the cellular immunity was also crucial to defend T. spiralis infection (Cui et al, 2013b;Liu et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…The splenocytes and MLN cells were prepared in the DMEM medium and their density were adjusted to 2 × 10 5 cells/ml. After the cells were stimulated with rTsASP2 at a concentration of 3 μg/ml at 37°C for 72 h, the culture supernatant was collected and the concentrations of cytokines (IFN-γ and IL-4) were measured using a sandwich ELISA method (Pompa-Mera et al, 2014;Zhang et al, 2020b).…”
Section: Cytokine Determinationmentioning
confidence: 99%
“…The structural domain and enzyme active sites of TsAAP (GenBank: KRY29491.1) were predicted and analyzed by using online webtool and CN3D software (Song et al, 2018b). The amino acid sequence of TsAAP gene was compared with AAP from different species /genotypes of Trichinella by using Clustal X (Zhang et al, 2020b). The GenBank accession numbers of AAP from Trichinella spp.…”
Section: Bioinformatics Analysis Of Tsaapmentioning
confidence: 99%